2022
DOI: 10.1038/s41377-022-01021-1
|View full text |Cite
|
Sign up to set email alerts
|

High-index-contrast photonic structures: a versatile platform for photon manipulation

Abstract: In optics, the refractive index of a material and its spatial distribution determine the characteristics of light propagation. Therefore, exploring both low- and high-index materials/structures is an important consideration in this regard. Hollow cavities, which are defined as low-index bases, exhibit a variety of unusual or even unexplored optical characteristics and are used in numerous functionalities including diffraction gratings, localised optical antennas and low-loss resonators. In this report, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Wet etching, thin film deposition, and photolithographyall standard semiconductor processeswere used to create an array of SiO 2 /AlO X double-shell HMs (see Materials and Methods, Figure a) . This fabrication did not undergo plasma etching for micron-depth patterning; instead, the thickness of the photoresist in use directly determined the height of HMs.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet etching, thin film deposition, and photolithographyall standard semiconductor processeswere used to create an array of SiO 2 /AlO X double-shell HMs (see Materials and Methods, Figure a) . This fabrication did not undergo plasma etching for micron-depth patterning; instead, the thickness of the photoresist in use directly determined the height of HMs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Wet etching, thin film deposition, and photolithography�all standard semiconductor processes�were used to create an array of SiO 2 /AlO X double-shell HMs (see Materials and Methods, Figure 2a). 33 This fabrication did not undergo plasma etching for micron-depth patterning; instead, the thickness of the photoresist in use directly determined the height of HMs. Scanning electron microscopy (SEM) images revealed that HMs were clearly formed without any inner residual photoresist, sustained by the heterogeneous oxide shells (Figure 2b and Supporting Information Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the morphological parameters of structure and its refractive index determine the strength of the electromagnetic field in light interacting with a material structure. [10][11][12][13][14] Hence, resonant scattering and absorption phenomena can be achieved by doping inorganic micro-nano particles with the size of the wavelength scales. Furthermore, particles with a low refractive index can form a higher refractive index difference with the substrate polymer, realizing superior optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with polymers, silicon-based materials, [16] inorganic oxides, [17,18] and chalcogenide glass [19] materials show high refractive index and low absorption loss, enabling a large degree of freedom in obtaining functional optical structures for strong optical confinement on flexible substrates. [20][21][22][23] It is innately advantageous to realize compact, flexible photonic devices using an inorganic-organic hybrid structure consisting of inorganic core material and organic cladding substrate. [24] Nowadays, the manufacturing processes of high-index-contrast (HIC) flexible integrated photonic devices are based on pattern transfer [25][26][27] and monolithic integration.…”
mentioning
confidence: 99%